IdDE: A collaborative environment for distributed programming in pairs - Gartner, V. C.; da Silva Pinto, S. C. C. (2012 XXXVIII Conferencia Latinoamericana en Informatica, 2012)
The theory of the pair more able, proposed by Vygotsky addresses the collaborative learning using pairs of people with different cognitive development, where the subject further developed can help and provide experiences to the partner so that his level of learning increases. Within the agile idea of pair programming implicitly obeys this theory. The idea of this paper is to provide that a larger set of people can share the development of a source code in a collaborative manner and the whole intellectual process that leads to changes in certain parts of a source code that the history will be record in the environment. This allows a N-N relationship can be established in a development environment for distributed software, leveraging the theory of the more capable peer. The article presents a tool developed as a NetBeans plug-in functionality that incorporates several of collaborative environments to support distributed programming in real time.